Factors Influencing the Implementation of Electronic Medical Record Systems at Bhayangkara Hospital and Benyamin Guluh Kolaka Hospital - Aknur, Rikha; Sunarsih, Sunarsih; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Electronic Medical Records (EMR) are a crucial technology for improving the efficiency and quality of healthcare services compared to manual, paper-based systems. This study compares the implementation of EMRs at the Benyamin Guluh Hospital in Kolaka and Bhayangkara Hospital in Kendari to evaluate differences in efficiency and quality of healthcare services after the implementation of EMRs. Method: This study employed a qualitative approach with phenomenology. The researcher served as the key instrument, with data collection techniques including in-depth interviews and participant observation. The study population consisted of IT directors and staff as primary informants, as well as doctors, nurses, laboratory personnel, pharmacists, and patients as regular informants. The sample was drawn using purposive sampling. Data were collected from 14 informants and analyzed inductively. Result: Bhayangkara Kendari Hospital has made significant progress in integrationElectronic Medical Records, with adequate technological infrastructure, fast and secure data access, and comprehensive staff training. In contrast, Benyamin Guluh Hospital in Kolaka faces challenges related to inadequate infrastructure and challenges in training and network quality. Despite progress in reducing paper use and improving coordination between units, technical issues and inadequate training impact efficiency and patient satisfaction. Conclusion: The needs of both hospitals include improving information technology infrastructure, regular and comprehensive training, policy evaluation and adjustment, improving data management and security, and increasing coordination between institutions.